2018
DOI: 10.1007/s12471-018-1124-2
|View full text |Cite
|
Sign up to set email alerts
|

Competence of general practitioners in requesting and interpreting ECGs - a case vignette study

Abstract: BackgroundPerforming electrocardiography is common in general practice, but the quality of indication setting and diagnostic accuracy have been disputed.ObjectivesTo assess the competence of general practitioners (GPs) in their decision-making process with regard to recording and interpreting an electrocardiogram (ECG) and evaluating the relevance of the result for management.MethodsAn online case vignette survey was performed among GPs and cardiologists (in 2015). Nine cases describing situations for which Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 21 publications
(31 reference statements)
1
22
0
Order By: Relevance
“…GPs judged that they have sufficient knowledge and experience to diagnose AF. Research by Compiet et al shows that the diagnostic accuracy of GPs to detect AF is indeed high (96%) [15]. When comparing current results to our previous study among cardiologists, we see that monitoring devices are more often available to cardiologists than to GPs, as is to be expected [12].…”
Section: Discussionsupporting
confidence: 79%
“…GPs judged that they have sufficient knowledge and experience to diagnose AF. Research by Compiet et al shows that the diagnostic accuracy of GPs to detect AF is indeed high (96%) [15]. When comparing current results to our previous study among cardiologists, we see that monitoring devices are more often available to cardiologists than to GPs, as is to be expected [12].…”
Section: Discussionsupporting
confidence: 79%
“…3). In addition, our previous vignette study on the competence of GPs in requesting and interpreting ECGs revealed that GPs showed poor diagnostic accuracy for left anterior fascicular block and incomplete right bundle branch block [24].…”
Section: Discussionmentioning
confidence: 99%
“…We expect these will support future ECG training for GPs. The first study addressed the competence of GPs in requesting and interpreting ECGs by means of a case vignette study [24]. In the remaining three studies, we have focussed on the performance of GPs in various real-life situations: ECGs recorded during out-of-office hours (to be published), ECGs performed during primary care cardiovascular risk management programmes (to be published) and ECGs carried out in symptomatic patients during day-care practice (this study).…”
Section: Introductionmentioning
confidence: 99%
“…The GPs also described false abnormalities in the ECG tracings. 7 The implication of these study findings was that areas of poor competence amongst the GPs could be established and followed by appropriate intervention measures.…”
Section: Introductionmentioning
confidence: 88%